التفسير المقارن لسورة آل عمران من الآية الواحد وثلاثون إلى الآية خمسون "31-50" - قده أماني (University of Eloued جامعة الوادي, 2024)
"ملخص البحث تتناول هذه المذكرة التفسير المقارن لسورة آل عمران من الآية 31 إلى 50 دراسة نظرية تطبيقية, حتى أطبق عليها خطوات التفسير المقارن. فقد قمت بلمحة تعريفية لتفسير المقارن وتعريف لسورة آل عمران, حيث تطرقت من خلال هذه الدراسة لهذه الآيات إلى خمس مواضع, اختلف فيها المفسرين اختلافا حقيقيا معتبرا, فعرضت فيها أقوال المفسرين, وأصحابها, مع أدلتهم, ثم مناقشة الأقوال مع الأدلة, ثم بينت القول الراجح منها. ومن خلال هذا البحث توصلت إلى عدة نتائج أهمها: تكمُن أهميّة التفسير المقارن في القدرة على إيجاد ملكة التفسير التي تتحقّق من شتّى العلوم المختلفة والمعارف, والقول الراجح عند المفسرون في قوله تعالى: {فَنَادَتْهُ الْمَلَائِكَةُ}، جمع ملائكة. "Research Summary This research aims to provide a comparative interpretation of Surah Al-Imran, verses 31 to 50, through a theoretical and applied study. The goal is to apply the steps of comparative interpretation to these verses. The study includes an introductory overview of comparative interpretation and an introduction to Surah Al-Imran. It examines five instances within these verses where there is significant, substantive disagreement among the interpreters. The study presents the views of the interpreters and their proponents, along with their evidence, followed by a discussion of these views and their evidence, and then identifies the most likely correct interpretation. Through this research, several conclusions were reached, the most important of which is: the significance of comparative interpretation lies in its ability to develop the interpretative skill that is enriched by various sciences and knowledge. The most likely correct interpretation among the interpreters for the verse {فَنَادَتْهُ الْمَلَائِكَةُ} is that it refers to the gathering of angels.
Keywords: التفسير المقارن"; "الاختلاف"; "الترجيح"; "آل عمران".; "Comparative Interpretation"، "Difference"، "Preponderance"، " Al-Imran "